Panel Design and Optimization for High‐Dimensional Immunophenotyping Assays Using Spectral Flow Cytometry. Issue 1 (5th March 2020) - Ferrer‐Font, Laura; Pellefigues, Christophe; Mayer, Johannes U.; Small, Sam J.; Jaimes, Maria C.; Price, Kylie M.
Abstract: Technological advances in fluorescence flow cytometry and an ever‐expanding understanding of the complexity of the immune system have led to the development of large (20+ parameters) flow cytometry panels. However, as panel complexity and size increase, so does the difficulty involved in designing a high‐quality panel, accessing the instrumentation capable of accommodating large numbers of parameters, and analyzing such high‐dimensional data. A recent advancement is spectral flow cytometry, which in contrast to conventional flow cytometry distinguishes the full emission spectrum of each fluorophore across all lasers, rather than identifying only the peak of emission. Fluorophores with a similar emission maximum but distinct off‐peak signatures can therefore be accommodated within the same flow cytometry panel, allowing greater flexibility in terms of panel design and fluorophore detection. Here, we highlight the specific characteristics of spectral flow cytometry and aim to guide users through the process of building, designing, and optimizing high‐dimensional spectral flow cytometry panels using a comprehensive step‐by‐step protocol. Special considerations are also given for using highly overlapping dyes, and a logical selection process for optimal marker‐fluorophore assignment is provided. © 2020 by John Wiley & Sons, Inc.